(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
Currently, productive organizations face an era of constant challenges related to the adaptation of their processes to the new productive paradigm of intelligent industries, globalized markets, high competitiveness and product customization. Under this scenario, operational excellence methodologies integrated with digital twin technologies play a leading role in improving business performance and generating competitive advantages. The present work proposes as a central axis of research the joint application of the TLS model (TOC, Lean, Six Sigma) with discrete event simulation techniques and experimental designs, as a basis to generate an improvement in the productive capacity of a porcelain tile line. in a ceramic industry, located in the province of Buenos Aires. The methodology used for its development consists of four (4) main phases. A first phase of characterization of the process and quantification of resources for the development of a conceptual model. A second phase of development and validation of the computational model, using FlexSim® as a simulation tool. A third phase of diagnosis, where through the VSM technique and the theory of restrictions, the cooking operation was identified as the bottleneck of the system. And a last phase, analysis, in which, through a unifactorial experiment design, different scenarios were evaluated to enhance the productive capacity of the line by implementing changes in the current structure of the furnace.